Inshore biogeochemical samples collected from Disko Fjord and Saqqarleq Fjord during August 2022 - Hopwood, Mark James; Ruan, Yaqing; Achterberg, Eric Pieter (PANGAEA, 2025)
In parallel with a summertime cruise in Disko Bay (GLICE, August 2022), small vessels were used to sample the meltwater-rich areas at the entrance of Disko Fjord and in Saqqarleq Fjord (the southern branch of the Icefjord system). Discrete samples were collected from surface fjord waters and GO-FLO bottles were deployed down to 40 m to collect short profiles through the salinity stratified surface layer. Samples were retained for nutrients and dissolved trace metals. Surface water properties were determined using a YSI EXO-1 sensor to provide salinity, temperature, chlorophyll and turbidity data. A SBE 911plus CTD (Seabird) was used to conduct profiles down to 40 m. CTD bottle files are presented with discrete macronutrient and trace metal concentrations. Macronutrient samples were frozen and analyzed via autoanalyzer upon return to GEOMAR. Trace metal samples were filtered, acidified and analyzed upon return to GEOMAR after offline preconcentration using a seaFAST system.
Keywords: Disko Bay; Fjord; Greenland; Meltwater; nutrients; trace metals